Histologic Evidence of Epithelial-Mesenchymal Transition and Autophagy in Human Fetal Membranes - Severino, Mary E; Richardson, Lauren S; Kacerovsky, Marian; Menon, Ramkumar (The American journal of pathology, 2024)
Preterm, prelabor rupture of the human fetal membranes (pPROM) is involved in 40% of spontaneous preterm births worldwide. Cellular-level disturbances and inflammation are effectors of membrane degradation, weakening, and rupture. Maternal risk factors induce oxidative stress (OS), senescence, and senescence-associated inflammation of the fetal membranes as reported mechanisms related to pPROM. Inflammation can also arise in fetal membrane cells (amnion/chorion) due to OS-induced autophagy and epithelial-mesenchymal transition (EMT). Autophagy, EMT, and their correlation in pPROM, along with OS-induced autophagy-related changes in amnion and chorion cells in vitro, were investigated. Immunocytochemistry staining of cytokeratin-18 (epithelial marker)/vimentin (mesenchymal marker) and proautophagy-inducing factor LC3B were performed in fetal membranes from pPROM, term not in labor, and term labor. Ultrastructural changes associated with autophagy were verified by transmission electron microscopy of the fetal membranes and in cells exposed to cigarette smoke extract (an OS inducer). EMT and LC3B staining was compared in the chorion from pPROM versus term not in labor. Transmission electron microscopy confirmed autophagosome formation in pPROM amnion and chorion. In cell culture, autophagosomes were formed in the amnion with OS treatment, while autophagosomes were accumulated in both cell types with autophagy inhibition. This study documents the association between pPROMs and amniochorion autophagy and EMT, and supports a role for OS in inducing dysfunctional cells that increase inflammation, predisposing membranes to rupture.
Keywords: zánět; Fetal Membranes, Premature Rupture; extraembryonální obaly; novorozenec; autofagie; předčasný odtok plodové vody; Autophagy; lidé; Female; Inflammation; ženské pohlaví; Humans; epitelo-mezenchymální tranzice; Epithelial-Mesenchymal Transition; Infant, Newborn; Extraembryonic Membranes